2005
DOI: 10.1111/j.1440-1711.2005.01378.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of oxidative stress in ERK and p38 MAPK activation induced by the chemical sensitizer DNFB in a fetal skin dendritic cell line

Abstract: SummaryThe intracellular mechanisms involved in the early phase of dendritic cell (DC) activation upon contact with chemical sensitizers are not well known. The strong skin sensitizer 2,4-dinitrofluorobenzene (DNFB) was shown to induce the activation of mitogen-activated protein kinases (MAPK) in DC. In the present study, we investigated a putative role for oxidative stress in DNFB-induced MAPK activation and upregulation of the costimulatory molecule CD40. In a DC line generated from fetal mouse skin, DNFB in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 47 publications
1
33
0
Order By: Relevance
“…TNF-α production induced by DNCB was also linked to the activation of p38 MAPK and JNK (Boisleve et al, 2004). In previous results performed with the foetal skin-derived dendritic cell line (FSDC), we reported that DNFB activates p38 MAPK and ERK1/2 via the production of reactive oxygen species and that protein oxidation plays an important role in MAPKs activation (Matos et al, 2005b). These results are in agreement with the key role of oxidative stress in the activation of MAPKs (Mizuashi et al, 2005;Hirota et al, 2009;Suzuki et al, 2009;Kagatani et al, 2010).…”
Section: Activation Of the Mitogen-activated Protein Kinases (Mapks)supporting
confidence: 78%
See 1 more Smart Citation
“…TNF-α production induced by DNCB was also linked to the activation of p38 MAPK and JNK (Boisleve et al, 2004). In previous results performed with the foetal skin-derived dendritic cell line (FSDC), we reported that DNFB activates p38 MAPK and ERK1/2 via the production of reactive oxygen species and that protein oxidation plays an important role in MAPKs activation (Matos et al, 2005b). These results are in agreement with the key role of oxidative stress in the activation of MAPKs (Mizuashi et al, 2005;Hirota et al, 2009;Suzuki et al, 2009;Kagatani et al, 2010).…”
Section: Activation Of the Mitogen-activated Protein Kinases (Mapks)supporting
confidence: 78%
“…Accordingly, DNFB induced a significant increase in protein oxidation, as measured by the formation of carbonyl groups, while it had almost no effect on lipid peroxidation in the FSDC line. In addition, glutathione, but not vitamin E, inhibited DNFB-induced p38 MAPK and ERK1/2 phosphorylation (Matos et al, 2005b). Whether sensitisers induce redox or oxidative stress in dendritic cells was investigated by measuring the ratio of the oxidised (GSSG) versus the reduced (GSH) form of cellular glutathione (Mizuashi et al, 2005); all of the sensitisers (nickel, formaldehyde, DNCB, MnCl 2 , and thimerosal), but none of the non-sensitisers (SDS, BC, and ZnCl 2 ), reduced the GSH/GSSG ratio, which was accompanied by p38 MAPK phosphorylation.…”
Section: Intracellular Redox Imbalance Changes In Cell Surface Thiolmentioning
confidence: 99%
“…It was also demonstrated that the redox imbalance induced by skin sensitizers is important in the regulation of DC functions [5,38,39,41,47,61]. Therefore, the increase in Trx-1 mRNA expression observed in .…”
Section: Discussionmentioning
confidence: 98%
“…Similarly to LPS, skin sensitizers can induce redox imbalance [38,41] that activates the cellular mechanism proposed above and responsible for the increase in Trx-1 protein levels. These data suggest that the ASK1/Nrf2/ ARE regulatory pathway could be activated by LPS and skin sensitizers in a similar way, being involved in DC maturation.…”
Section: Discussionmentioning
confidence: 99%
“…DCs upregulate expression of MHC class II molecules and costimulatory molecules such as CD40, CD54, CD83, and CD86 in vitro in response to contact sensitizers (9,(11)(12)(13). DNFB mediates production of reactive oxygen species (ROS) and activates p38 mitogen-activated protein kinase (MAPK) and ERK1/2 to regulate CD40 expression (14,15). However, exposure of DCs to nickel sulfate stimulates signal transduction pathways and augments expression of MHC class II and several costimulatory molecules in different manners compared to that of DNFB (16).…”
Section: Introductionmentioning
confidence: 99%